Employee Competency Development in the Personnel and Human Resources Development Agency: JEL Classification: O15, O19, M53, D73, H83, I28, J45 - Sitanggang, Charles Tua; Hamid, Muliyadi; Djabar, Sadly Abdul (Journal La Bisecoman, 2025)
This study aims to determine the efforts made by BKPSDM Nunukan Regency in improving employee competence. Increasing ASN competence is an important factor in improving work effectiveness and the quality of public services. BKPSDM has various programs and policies designed to develop employees' skills and knowledge to suit the needs of an ever-evolving bureaucracy. This research was conducted at the Nunukan Regency Personnel and Human Resources Development Agency (BKPSDM) using qualitative methods. Qualitative research is exploratory and aims to understand social phenomena in a natural and complex context. The data collection techniques used include interviews with relevant informants, observation of competency development activities, and document analysis to obtain more accurate and in-depth data. The results of the study indicate that the Nunukan Regency BKPSDM has implemented various strategic policies and programs in improving employee competency, from planning to post-training evaluation. Based on Rahmat's theory of competency development, improving the quality of human resources is carried out systematically through training, coaching, and continuous evaluation. BKPSDM emphasizes monitoring and evaluation as part of strengthening employee capacity. The implementation of this strategy shows that structured competency development can improve professionalism, work effectiveness, and the quality of public services in Nunukan Regency. Thus, the strategy implemented by BKPSDM can be a model for sustainable HR development in the government sector.